PENGARUH PEMBERIAN KOMPOS DAN CARA PENGAIRAN TERHADAP PERILAKU BESI PADA TANAH SAWAH DI DAERAH REGIM CURAH HUJAN TINGGI DI KABUPATEN POSO - Mowidu I; Sunarminto B. H.; Purwanto B. H.; Utami S. N. H. (AgriPeat, 2016)
The iron in the soil may be the form of crystalline, amorphous or organic. To assess the effect of compost and irrigation practices to form Fe in the soil, greenhouse experiments have been conducted using paddy soil of high rainfall regime in Poso. Experiment 2 factors consisted of factors compost 5 t ha-1 (K0: without compost, K1: straw compost 100%, K2: straw compost 75% + pod husks (ph) 25%, K3: straw compost 50% + ph 50%, K4: straw compost 25% + ph 75%, K5: pod husks 100%), and irrigantion practices factor (I1: saturated and I2: intermittent). Observation was made of the Fe-d, Fe-o and Fe-p using the selective solvent (0.1 M Na-pyrophosphate, 0.2 M ammonium oxalate pH 3, and Na-dithionite citrate pH 7.3). The results showed that significantly affect the application of compost to Fe-d and Fe-o at 14 days after planting (DAT), and the Fe-p at 40 and 70 DAT. Irrigation practices significantly effect on Fe-o at 70 DAT and harverst time, the Fe-p at 40, 70, 75 DAT and harverst time, wherewas the Fe-d effect not significant. Watering saturated lead levels of fe-o and Fe-p higher. The interaction between the application of compost and irrigation practices significantly affect to Fe-d and Fe-p at harvest, while the Fe-o effect is no signicant. Fe-d levels highest in K4I1 at harvest were significantly different with straw compost applications with higher composition and water saturation, as well as the applications of compost pod husks composition higher and intermittent irrigation. Fe-p levels were lower in K0I1 and significantly different from the composting with different compositions